Estimation of Mean Hemoglobin, Anemia Prevalence, and Associated Risk Factors Among Medical Students: Prevalence of anemia among medical students - Noor, Amna; Liaqat, Aminah; Fatima, Abeer; Areeba; Khan, Aamna; Ahmed, Abiha (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Abstract Background: Anemia is one of the most common types of blood disorders affecting twice as many as females as males. Anemia reduction is one of six World Health Assembly Global Nutrition Targets within the Comprehensive Implementation Plan on maternal, infant, and young child nutrition. Anemia caused by iron deficiency in women of reproductive age of 15-24 years increases the risk of maternal mortality and impaired fetal growth. It is important to promote dietary intake of iron rich food to compensate for menstrual iron losses. Therefore, this study aims at raising awareness, highlighting risk factors, to assess the mean hemoglobin levels of the students and the prevalence of anemia among students at Rawalpindi Medical University. Materials and Methods: This is an observational cross-sectional study conducted among 110 undergraduate students of age 18 to 25 years at Rawalpindi Medical University by using a convenient sampling technique. Hemoglobin levels assessed using an automated CP analyzer were included. Data was collected by verified self-grading anemia questionnaire on Google Forms and analyzed using IBM SPSS software version 26. Anemia and nutritional indicators correlation was determined by Chi-square. Results: In a total of 110 students, the frequency of non-anemic students was 1.75 times more than anemic students of 92.5% anemic students were female and 7.5% were males which suggesting that anemia is more prevalent in females than males. Among female 42% and that of male 14% were anemic. Our study demonstrates that the estimated value of mean hemoglobin in the studied population is 11.87mg/dl. Hemoglobin levels were significantly lower in females with heavy menstrual flow than those with normal flow. Among those who took iron a few times in their diet, 77.5% were anemic. However, BMI, socioeconomic status, and hostelite/ non-hostelite status did not have a significant relation. Conclusion: The research conclusively demonstrates a higher prevalence of anemia among female medical students (92.5%) compared to their male counterparts (7.5%). The female population is particularly vulnerable to anemia due to heavy menstruation and insufficient iron intake. Our findings on the prevalence of anemia among RMU students indicate a pressing need for awareness programs focused on anemia and its preventive measures.